Cucurbit Powdery Mildew: First Insights for the Identification of the Causal Agent and Screening for Resistance of Squash Genotypes (Cucurbita moschata (Duchesne ex Lam.) Duchesne ex Poir.) in Mendoza, Argentina - Caligiore Gei, Pablo Fernando (2022)
The cucurbit powdery mildew (CPM) caused by different fungal species is a major concern for cucurbit crops around the world. In Argentina CPM constitutes the most common and damaging disease for cucurbits, especially for squash crops (Cucurbita moschata). The present study displays initial insights into the knowledge of the disease in western Argentina, including the determination of the prevalent species causing CPM, as well as the evaluation of the resistance of squash cultivars and breeding lines. Fungal colonies were isolated from samples collected in Mendoza province, Argentina. A field trial was also performed to assess the resistance of five squash accessions, including commercial cultivars and breeding lines. The severity of CPM was analyzed and epidemiological models were built based on empirical data. The morphological determinations and analysis with specific molecular markers confirmed Podosphaera xanthi as the prevalent causal agent of CPM in Mendoza. The results od the field trial showed differences in the resistance trait among the squash accessions. The advanced breeding line BL717/1 showed promising results as source of CPM resistance for the future development of open pollinated resistant cultivars, a crucial tool for an integrative control of the disease.